Paths Chosen and Lessons Learned: Pages for a Shared Memory - Gudmundson, Lowell (2026)
In this article, Lowell Gudmundson shares an account of his career at the National University (UNA), in the context of the 50th anniversary of the Revista de Historia (History Journal). He recalls his arrival at the School of History in 1977, an experience interrupted by a few years of study abroad, but which he later resumed when he rejoined the journal as a teacher and editorial staff member. Throughout his narrative, he highlights figures such as Germán Tjarks, José Antonio Salas, and Patricia Alvarenga, among others, who not only contributed to the journal but also to national, regional, and international historiography. The author invites reflection on the development of the UNA School of History, encouraging the creation of themes that respond to new questions. He also highlights both the diversity of approaches that enrich the magazine and the versatility of the researchers trained at this institution.